2002
DOI: 10.1104/pp.004747
|View full text |Cite
|
Sign up to set email alerts
|

Early Embryo Development in Fucus distichusIs Auxin Sensitive

Abstract: Auxin and polar auxin transport have been implicated in controlling embryo development in land plants. The goal of these studies was to determine if auxin and auxin transport are also important during the earliest stages of development in embryos of the brown alga Fucus distichus. Indole-3-acetic acid (IAA) was identified in F. distichus embryos and mature tissues by gas chromatography-mass spectroscopy. F. distichus embryos accumulate [3H]IAA and an inhibitor of IAA efflux, naphthylphthalamic acid (NPA), elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
69
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 60 publications
(52 reference statements)
5
69
0
1
Order By: Relevance
“…Duncan's multiplerange post hoc test showed that LatB at 30 and 100 nM was significantly different from the control (P # 0.005). The elevated IAA accumulation is consistent with a reduction of IAA efflux, and the magnitude of the LatB effect parallels the NPA effect on IAA accumulation in Figure 5 and as previously reported (Basu et al, 2002).…”
Section: An Intact Actin Cytoskeleton Is Needed For Embryo Polarizatisupporting
confidence: 71%
See 4 more Smart Citations
“…Duncan's multiplerange post hoc test showed that LatB at 30 and 100 nM was significantly different from the control (P # 0.005). The elevated IAA accumulation is consistent with a reduction of IAA efflux, and the magnitude of the LatB effect parallels the NPA effect on IAA accumulation in Figure 5 and as previously reported (Basu et al, 2002).…”
Section: An Intact Actin Cytoskeleton Is Needed For Embryo Polarizatisupporting
confidence: 71%
“…Although the presence of IAA in algae so far appears to be universal, the function and transport of IAA have been tested in very few species (Cooke et al, 2002), and sometimes with contradictory findings (Dibb-Fuller and Morris, 1992;Klämbt et al, 1992). In F. distichus, previous evidence has demonstrated that IAA is present and that IAA accumulation is modulated by IAA efflux inhibitors (Basu et al, 2002). Finally, IAA and IAA efflux inhibitor treatment alter F. distichus embryo developmental patterns (Basu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations